Cybersecurity and Security of the Banking Business Under Martial Law - Serhii Azarenkov (Фінансово-кредитні системи: перспективи розвитку.)
The relevance of the research topic lies in the need to find solutions for the cybersecurity of the banking business, thereby enhancing the overall security of banking operations. The purpose of this study is to establish the importance of cybersecurity in ensuring the security of the banking business and the development of banks in the modern digital space. To achieve this goal, a structural-logical and systemic approach was used to construct a model for ensuring banking cybersecurity. Additionally, systematization and grouping methods were applied to characterize cyberattacks and their consequences, as well as to systematize regulatory and legal acts on banking security and cybersecurity. The object of the study is the process of ensuring banking cybersecurity and its integration into the overall banking security system. The main focus of the study is to identify emerging threats to banking security and cybersecurity, as well as to determine the challenges banks face when forming cybersecurity systems, including the use of artificial intelligence, security issues related to cloud technologies, digitalization of banking business processes, and third-party security risk management. The obtained results can be used to improve the cybersecurity system of the banking business and its integration into the general system of corporate banking governance. The study's conclusions emphasize the necessity of incorporating international cybersecurity standards into national regulatory frameworks. Moreover, the findings can contribute to the development of a tailored approach to building a cybersecurity model for banks, which should include principles, implementation measures, quality assessment approaches, and a cooperative cybersecurity strategy.